Fasciola hepatica infection in children actively detected in a survey in rural areas of Mardan district, Khyber Pakhtunkhawa province, northern Pakistan. (April 2019) - Qureshi, Asma W.; Zeb, Aurang; Mansoor, Abu; Hayat, Azam; Mas-Coma, Santiago
Abstract: Human fascioliasis is a freshwater snail borne, zoonotic disease caused by Fasciola liver flukes which are widely spread throughout Pakistan and has recently proved to be endemic in humans of the Punjab province. To verify whether fasciolids are also affecting humans outside this province, studies were conducted in four communities comprising rural and urban areas of Mardan district, Khyber Pakhtunkha province, northern Pakistan. Activities comprised two surveys, a coprological one to look for Fasciola infection and another to get information on potential human infection sources and risk factors by means of a questionnaire. Out of 540 subjects of all ages surveyed, only 4 children (0.74%) were found positive for Fasciola eggs: two 9- and 13-year old boys and two 7- and 16-year old girls. Burden per child ranged 73–146 eggs per gram of faeces (epg), with an average of 106 ± 15.4 epg. Based on the egg size, the infection was diagnosed to be caused by F. hepatica . Serum analyses showed eosinophilia and elevated enzyme values in liver function tests. The Mardan area fits well to all transmission and epidemiological requirements of F. hepatica, namely the presence of infected livestock reservoirs throughout, the appropriate climatic factors (mainly monthly temperature variation along the year), and the existence of adequate freshwater collections. The existence of the specific lymnaeid snail vector species for F. hepatica transmission was reported in the neighbouring Swat valley time ago. Results show that human fascioliasis may be widespread in Pakistan and that both F. hepatica and F. gigantica may be involved. Graphical abstract: Unlabelled Image Highlights: Coprological survey in Mardan district, Khyber Pakhtunkha province, northern Pakistan. Four children infected by Fasciola hepatica among 540 subjects surveyed. Mardan area fits to all transmission and epidemiological requirements of F. hepatica. Questionnaire survey showed high risk factors for liver fluke transmission. Human fascioliasis by F. hepatica and F. gigantica may be widespread in Pakistan.